2022
DOI: 10.1021/acs.biochem.2c00379
|View full text |Cite
|
Sign up to set email alerts
|

Transposons and CRISPR: Rewiring Gene Editing

Abstract: CRISPR-Cas is driving a gene editing revolution because of its simple reprogramming. However, off-target effects and dependence on the double-strand break repair pathways impose important limitations. Because homology-directed repair acts primarily in actively dividing cells, many of the current gene correction/replacement approaches are restricted to a minority of cell types. Furthermore, current approaches display low efficiency upon insertion of large DNA cargos (e.g., sequences containing multiple gene cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…11,13 Newer gene-editing strategies may require even more complex mixtures of additional proteins or large donor-DNA sequences, which require additional optimization. 14 There is, therefore, a significant need for modular, high-capacity, cargo-agnostic delivery systems for gene editing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 Newer gene-editing strategies may require even more complex mixtures of additional proteins or large donor-DNA sequences, which require additional optimization. 14 There is, therefore, a significant need for modular, high-capacity, cargo-agnostic delivery systems for gene editing.…”
Section: Introductionmentioning
confidence: 99%
“…RNPs thus present challenges due to a more diverse charge distribution and Cas9 enzyme sensitivity to denaturation. It has been recently shown that LNP formulations should therefore be independently optimized for RNP delivery rather than directly using systems previously optimized for RNA delivery. , Newer gene-editing strategies may require even more complex mixtures of additional proteins or large donor-DNA sequences, which require additional optimization . There is, therefore, a significant need for modular, high-capacity, cargo-agnostic delivery systems for gene editing.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the connection between Tn7-like transposons (See Glossary) and CRISPR is discovered [16], with subsequent observations revealing associations with various CRISPR types, including I-B, I-D, I-F, and V-K [17][18][19][20][21][22]. In 2019, the type V-K [17] and type I-F3 [18] CRISPRassociated transposons (termed CASTs) are first repurposed for DSB-free, RNA-guided DNA insertion into E. coli, which implicates the potentials of CASTs to obviate the requirement of DSB induction in CRISPR-Cas systems.…”
mentioning
confidence: 99%
“…Several articles have comprehensively reviewed CASTs, either offering a general introduction [25][26][27][28] or delving into specific aspects like molecular mechanisms [20,21,29] and applications related to DSB-free DNA integration [28,30,31]. Yet OMEGA system is reviewed in only two papers [21,32] and several research spotlight articles [33][34][35].…”
mentioning
confidence: 99%
“…As a result, we have witnessed many breakthroughs, from the development of designer nucleases to their use in microbes, animals, humans, and agricultural plants ( Adli, 2018 ; Zhang et al, 2019 ; Anzalone et al, 2020 ; Li et al, 2023 ; Wang and Doudna, 2023 ). More recently, to improve the editing accuracy and precision and reduce dependence on the cell’s developmental state, new approaches, such as the OMEGA (obligate mobile element-guided activity), CAST (CRISPR-Cas-associated transposon), and INTEGRATE (insertion of transposable elements by guide RNA-assisted targeting), were developed and tested in different organisms ( Tenjo-Castaño et al, 2022 ). Further, CRISPR technology was deployed in imaging, diagnostics ( Wang and Doudna, 2023 ), and treatment of major human disorders ( Wang and Doudna, 2023 ).…”
mentioning
confidence: 99%